Friendship, dialogue and interiority in the question of Indian nationalism - Visvanathan, Susan (2002)
In the second decade of the last century, as the world limped back from a long-drawn war and India found itself on the verge of a new wave of anti-imperalist struggle, a strange friendship was forged between three unusual men. This paper looks at the friendship between Mahatma Gandhi, C.F. Andrews and S.K. Rudra against the backdrop of such tumultuous times. Through letters and records that still stand as testimony to their friendship, this paper analyses issues of freedom of choice, and implications of nationality. - Reproduced.
Keywords: Gandhi, M.K.; Andrews, C.F.; Rudra, S.K.; Nationalism - India; History